Business Coaching of a Local F&B MSME: Building Financial Projection for External Funding and Measuring Digital Marketing Activities - Fatih, Alan; Fachrizah, Hilda (AIBPM Publisher, 2021)
Despite a large number of MSMEs in Indonesia, the contribution of the MSMEs to the country's GDP is relatively low. Some of the obstacles faced by MSMEs in Indonesia include access to capital, human resources, and supporting facilities. These obstacles were also faced by one of the local MSMEs, for instance Food and Beverage industry/service (F&B) that wanted to expand its business but was constrained by access to capital. Furthermore, the lack of evaluation of the performance of MSMEs is also a crucial problem, resulting in the lowest performance improvement plan. This paper describes a business coaching program for one of the local F&B MSMEs by building the financial projection and measuring digital marketing activities. Thus, MSMEs can be more accountable in seeking funding and evaluate their digital marketing performance continuously. This business coaching program is expected to increase access to capital and increase the productivity of MSMEs in Indonesia. By building financial projection and measuring digital marketing, MSME can define more specific targets and evaluate its attainment regularly. In order to accelerate the competence of MSMEs to be more competitive and productive, support from various parties is needed to overcome their obstacles.